Combined radiation therapy and surgery for esophageal cancer - Praderi, Luis; Parada, Ricardo (Cirugía del Uruguay, 1972)
The authors point out the advantages of preoperatory radiotherapy followed by surgical exeresis, in the case of neoplasms of the esophagus. The reasons for combining these procedures are stated; the techniques and tactics used in 14 cases which were treated with satisfactory results, are described in detail.